Pengembangan Perangkat Pembelajaran Berbasis Problem Based Learning Untuk Memfasilitasi Kemampuan Penalaran Matematis - Syef Harapit; Maimunah; Nahor Murani Hutapea (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2022)
This research is motivated by the limitations of mathematics learning tools to support learning in the 2013 Curriculum. This research aims to produce products in the form of learning tools (syllabus, RPP and LKPD) on SPLTV material for class X SMA with PBL models that meet valid and practical criteria to facilitate students' abilities. The learning device was developed using a 4D model. The development that the researchers carried out consisted of 4 stages, namely: (1) define; (2) design; (3) development; (4) dissemination. The research instrument consists of a validity instrument and a practical instrument. The validity instrument is in the form of a validation sheet to assess the feasibility of the syllabus, lesson plans and worksheets and a practical instrument in the form of a student response questionnaire to determine the readability of the LKPD. Expert validation results show that the product in the form of learning tools reaches the very valid category with average results for the syllabus 92%, lesson plans 93% and LKPD 90%. The learning tools being tested were LKPD categorized as very practical in small group trials with an average student response of 85% in the very practical category.